(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The predominant serovars of Salmonella associated with environmental contact surfaces and utensils used in processing and selling roasted chicken in Dutse town of Jigawa State was determined. The aerobic plate count of the one hundred (100) cotton swab samples collected from studied surfaces was determined. Cultural Identification of the isolates was done on Salmonella-Shigella agar (SSA) followed by microscopy. Biochemical confirmatory tests and serological tests using polyvalent and monovalent sera were conducted. Antibiotic sensitivity pattern of the isolates was determined by the Kirby Bauer disc diffusion method. Thirteen (13) samples yielded growth of Salmonellaserotypes, giving a prevalence rate of 13.0%. S. enteritidisserotype was the most identified (46.0%) while S. Virchow (8.0%) was the least. The highest bacterial load was observed on the hands of vendors, with an aerobic plate count of 4.4 ×104 CFU/g while the least was observed on cutting board utensil (2.5×104 CFU/g). Rate of contamination was found to be most significant on hand swab samples (38.0%) and least on knife swab samples (8.0%). Isolates were most susceptible to Chloramphenicol and Gentamicin but highly resistant to Septrin, Peflacin, and Tarivid. The hands, contact surfaces and utensils used in the processing of roasted chicken must be adequately sanitized with appropriate sanitizers so as to prevent the dissemination of pathogens such as Salmonella to consumers